Asosiasi Indikator Keuangan dengan Pelaporan Going Concern Emiten Non-Keuangan Bursa Efek Indonesia - Ananda Putra Fajar; Marsellisa Nindito; Hafifah Nasution (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2026)
This study examines the associations of cash flow, interest coverage ratio, firm growth, profitability, leverage, and liquidity with going concern reporting among non-financial companies listed on the Indonesia Stock Exchange during 2023–2024. The sample consists of 462 firm-year observations from 233 companies. Logistic regression is estimated with standard errors clustered at the company level and controls for firm size, year, and industry sector. Robustness checks include winsorization, exclusion of extreme observations, and a nonlinear liquidity specification. The results show negative associations for the interest coverage ratio and firm growth, and positive associations for leverage and liquidity. Cash flow and profitability are not significant. Leverage and liquidity remain significant across all robustness checks, while the results for the interest coverage ratio and firm growth are sensitive to extreme values. Leverage and liquidity are the most stable financial indicators associated with going concern reporting.